Clinical response to crizotinib and emergence of resistance in lung adenocarcinoma harboring a MET c-Cbl binding site mutation. (January 2020) - Wiesweg, Marcel; Herold, Thomas; Metzenmacher, Martin; Eberhardt, Wilfried E.; Reis, Henning; Darwiche, Kaid; Aigner, Clemens; Stuschke, Martin; Herrmann, Ken; Nensa, Felix; Schildhaus, Hans-Ulrich; Schuler, Martin
Highlights: Crizotinib is effective in lung cancer harboring a MET c-Cbl binding site mutation. MET c-Cbl binding site mutations constitute a distinct subtype of exon 14 mutations. Targeted therapy should be offered to patients with cancer driven by such mutations. Abstract: Objectives: MET c-Cbl binding site mutations constitute about 2 % of MET exon 14 alterations in lung cancer. Preclinical data suggests regarding these mutations as functional analogs of MET exon 14 skipping mutations, but clinical validation is lacking. Results: We report the case of a patient with metastastic lung adenocarcinoma harboring a c-Cbl binding site alteration and demonstrate clinical, radiological and metabolic response to crizotinib with a PFS of 10.6 months. As escape mechanism, a typical MET resistance mutation could be identified. Conclusion: MET c-Cbl binding site mutations should be regarded as a distinct subtype of MET exon 14 alterations. Patients with lung cancer harboring such mutations should be offered targeted therapy.